PENGARUH WAKTU DAN LETAK PEMANGKASAN DAUN TERHADAP PRODUKSI DAN KANDUNGAN GULA TANAMAN JAGUNG MANIS (Zea mays L. Saccharate Sturt) - Rahman, A. Adlu; Haris, Abdul; Sabahannur, St. (Percetakan Umi Toaha Makassar, 2024)
The study aims to determine the effect of leaf pruning time on the production and sugar content of sweet corn plants, analyze the effect of the location of sweet corn leaf pruning that provides the best production and sugar content, and analyze the effect of the interaction between leaf pruning time and pruning location on the production and sugar content of sweet corn plants. The study was conducted in January - March 2024 in an experimental field at the Gowa Agricultural Development Polytechnic (POLBANGTAN) Campus, Romanglopoa Village, Bontomarannu District, Gowa Regency. This study was conducted using a randomized block design (RBD) consisting of two factors. The first factor is the pruning time which consists of 3 levels: Leaf pruning at the age of 30 Day After Planting (DAP); Leaf pruning at the age of 40 DAP; and Leaf pruning at the age of 50 DAP. The second factor is the location of leaf pruning which consists of 3 levels, namely: Pruning 3 upper leaves; Pruning 3 lower leaves, and Pruning 1 upper leaf and 2 lower leaves. The results showed that pruning the three upper leaves at the age of 50 DAP produced the weight of the cob with the heaviest husk of 420.00 g and was significantly different from other treatments at the same age. The treatment between pruning at the age of 50 DAP and pruning the three upper leaves significantly affected the characteristics of sweet corn cobs, namely the diameter of the cob with the highest husk reaching 50.72 mm. The treatment of pruning at the age of 50 DAP with pruning the three upper leaves also affected the sugar content, with a brix content value reaching 15%, which was significantly different from other treatments at the same age.